A CLINICAL STUDY ON THE ROLE OF ERANDA KSHARA IN STHAULYA (OBESITY) - Borse Vilas Pundlikrao; Bhaskare Sunil A; Pawar Kiran Bhikaji; Meshram Dnyaneshwar Sudhakar (International Journal of Ayurveda and Pharma Research, 2015)
There are so many basic concepts in Ayurveda; Dhatvagni mandya is one of them. The whole phenomenon of disease cannot be completed without Dosha-Dushya Siddhant. They play important role in the pathology of disease. Obesity is one of them, which affect the health as well as life span. Sthaulya is one of the disease which is known to mankind since Vedic era, has been dealt in great details in Ayurvedic texts. The sign, symptoms and etiological factor of Sthaulya show very much resemblance with obesity. Worldwide Obesity is emerging health problem. It is a metabolic disorder which has affected every corner of world. In present study 30 patients of Sthaulya were selected from OPD and IPD of M.A. Podar hospital, Mumbai. These patients were undergone throw laboratory investigations. They were treated with Eranda Kshara with Ghrita bharjit Hingu given orally, duration of treatment was two months and follow up was done with parameters like Height, weight, BMI, Mid arm circumference, Waist circumference, Waist Hip ratio and symptoms of Sthaulya. It was observed that Atikshuda and Atitrushna reduce significantly. It shows relief in weight, BMI, Waist Circumference, Mid Arm Circumference and Waist Hip ratio. There was no significant change in hematological as well as Urine investigations. Average percentage of relief was 60.72%.